2001
DOI: 10.1103/physrevb.64.075307
|View full text |Cite
|
Sign up to set email alerts
|

Structure of metal-rich (001) surfaces of III-V compound semiconductors

Abstract: The atomic structure of the group-III-rich surface of III-V semiconductor compounds has been under intense debate for many years, yet none of the models agrees with the experimental data available. Here we present a model for the three-dimensional structure of the (001)-c(8ϫ2) reconstruction on InSb, InAs, and GaAs surfaces based on surface x-ray diffraction data that was analyzed by direct methods and subsequent least squares refinement. Contrary to common belief the main building blocks of the structure are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 38 publications
7
27
1
1
Order By: Relevance
“…Based on earlier studies, the presented topography structure image is recognized as the image of the surface indium sublattice, 13 where the dominant indium chains, labeled In1, protrude about 1.2 Å over the rest of the surface. It should be noted here that, according to a model of reconstructed ͑001͒ surfaces of AIIIBV semiconductor compounds, 24 the In1 atoms protrude of about 0.9 Å over the neighboring surface atoms. Thus, it is assumed that the imaging of the InSb͑01͒ surface in the constant detuning mode traces the surface with the relative changes of the tip-surface distance over atomic sites of about 0.3 Å.…”
Section: Fm-kpfm Of Insb(001) Surface Limits Of Lateral Resolutiomentioning
confidence: 99%
“…Based on earlier studies, the presented topography structure image is recognized as the image of the surface indium sublattice, 13 where the dominant indium chains, labeled In1, protrude about 1.2 Å over the rest of the surface. It should be noted here that, according to a model of reconstructed ͑001͒ surfaces of AIIIBV semiconductor compounds, 24 the In1 atoms protrude of about 0.9 Å over the neighboring surface atoms. Thus, it is assumed that the imaging of the InSb͑01͒ surface in the constant detuning mode traces the surface with the relative changes of the tip-surface distance over atomic sites of about 0.3 Å.…”
Section: Fm-kpfm Of Insb(001) Surface Limits Of Lateral Resolutiomentioning
confidence: 99%
“…Dimers can be formed by atoms of the same element (homodimers) or different elements (heterodimers). However, dimers can be formed also in the subsurface layer [27][28][29]. Thus, usually by dimer one means a pair of atoms which form a bond (in parallel to the surface) which is not characteristic for the underlying bulk.…”
Section: General Principles Behind Iii-v Semiconductor Surface Reconsmentioning
confidence: 97%
“…The atomic structure of these III-V(100)c(8 × 2) surfaces has been widely accepted to be one of the two structures shown in Fig. 10.10 or their combination [27][28][29]83]. The GaAs(100)c(8 × 2) surface has the ξ structure while the InAs(100)c(8 × 2) has the ξa structure rather than the ξ one.…”
Section: Bi-induced (2 × 1) Reconstructions On Iii-v(100) Surfacesmentioning
confidence: 99%
“…Subsequently, this predicted structure was confirmed by analyses of STM, low-energy electron diffraction, and surface x-ray diffraction. [21][22][23] In this novel structure, the excess Ga atoms are located below the surface layer. Thus, from the vacuum side the surface looks as if it is As rich.…”
Section: Introductionmentioning
confidence: 99%
“…Recently such reconstruction, though with a noticeable amount of disordered group-III surface vacancies, was also suggested to exist for other III-V surfaces such as InAs and InSb. 22,23 The adsorption and etching processes of the GaAs surface with Cl, the most common etchant, has been extensively investigated in the literature, and Cl 2 is known to adsorb dissociatively. 3,4,7,24,25 Recently McLean et al reported a systematic STM study on chlorine adsorption and diffusion on GaAs͑001͒ c(8ϫ2).…”
Section: Introductionmentioning
confidence: 99%